Monte Carlo simulations and photoacoustic experiments to compare imaging depth at 532 nm, 800 nm, and 1064 nm - Sharma, Arunima (2021)
Photoacoustic imaging (PAI) is a rapidly growing imaging modality which offers the advantages of good optical contrast and high ultrasound resolution. Although PAI provides imaging depth beyond the optical diffusion limit, penetration depth in biological samples is limited due to absorption and scattering of light in tissues. Improvement in imaging depth has been achieved by irradiating the sample with laser pulses of near infrared-I (NIR-I) region (700 nm-900 nm) due to decreased scattering of light in tissues within this optical window. Recently, further improvement in imaging depth has been reported by irradiating the sample in near infrared-II (NIR-II) region (900 nm-1700 nm). In this work, imaging depth in breast tissues when samples were irradiated by wavelengths in different optical windows has been compared. Initially, Monte Carlo simulation for light propagation in biological tissues was performed to compute imaging depth for excitation wavelengths of 532 nm, 800 nm, and 1064 nm. Further, photoacoustic tomography at 532 nm, 740 nm, and 1064 nm and acoustic resolution photoacoustic microscopy at 570 nm and 1064 nm were conducted to validate the results. We have shown that maximum imaging depth is achieved by NIR-I (740 nm/800 nm) when surface energy for all wavelengths is kept constant. However, when the energy density is proportional to maximum permissible exposure (MPE) at corresponding wavelength, maximum imaging depth is achieved by 1064 nm (NIR-II window). Therefore, we conclude that increased MPE in NIR-II window is responsible for the improved penetration depth in breast tissue in this region.